Integrated Curriculum Management in the Full Day School Program at SDIT Sahabat Quran Koba Central Bangka - Rahmatika, Apryani; Arafat, Yasir; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2024)
The research aims to analyze integrated curriculum management in the full-day school program at SDIT Sahabat Quran Koba Central Bangka, which includes planning curriculum activities, organizing curriculum activities, implementing curriculum activities, evaluating curriculum activities, and supporting and inhibiting factors faced in implementing an integrated curriculum. The research carried out was a descriptive qualitative type of research using data collection techniques using interview and field observation methods. The results of this research show: 1) Planning for implementing an integrated curriculum at the Sahabat of the Qur’an Integrated Islamic Elementary School consists of three stages, namely preparation, planning, and structural organization; 2) The implementation of the curriculum is divided into two levels, namely: implementation of the school-level curriculum and the typical content of SD IT Sahabat of the Qur’an; 3) Organizing the curriculum consists of dividing teachers’ teaching duties and dividing study hours; 4) The evaluation carried out includes curriculum evaluation and implementation evaluation. Implementation evaluation consisting of program evaluation, evaluation of social development and student attitudes, evaluation of learning achievements in class, and evaluation of the achievement of the typical content of SD IT Sahabat of the Qur’an; 5) Supporting and inhibiting factors; Supporting factors for integrated curriculum management in the Full Day School program include: good coordination between institutions, commitment to all school components, supportive school atmosphere and activities, and good communication between the school and the parents. Meanwhile, inhibiting factors for curriculum activities include: facilities and infrastructure that are still not neatly arranged, the density of material provided, the density of school programs and teacher changes that often occur in each new school year and the school not yet joining the Integrated Islamic School Network.